Impact of electrically assisted bicycles on physical activity and traffic accident risk: a prospective observational study. Issue 4 (11th October 2022) - Haufe, Sven; Boeck, Hedwig Theda; Häckl, Sebastian; Boyen, Johanna; Kück, Momme; van Rhee, Clara Catharina; Graf von der Schulenburg, Johann-Matthias; Zeidler, Jan; Schmidt, Torben; Johannsen, Heiko; Holzwart, Dennis; Koch, Armin; et al.
Abstract : Background: Electrically assisted bicycles (e-bikes) have become increasingly popular and may facilitate active commuting and recreational cycling. Objective: To evaluate the physical activity levels and usage characteristics of e-bikers and conventional cyclists under real-world conditions. Methods: We conducted a prospective observational study in Germany to examine the effects of e-biking compared with conventional cycling on reaching the World Health Organization (WHO) target for physical activity—at least 150 min of moderate-to-vigorous physical activity (MVPA) per week. Study participants (1250 e-bikers and 629 conventional bike users) were equipped with activity trackers to assess the time, distance and heart rate during cycling over four consecutive weeks. Questionnaires were used to assess any traffic accidents incurred over 12 months. Results: The proportion of participants reaching 150 min of MVPA per week was higher for conventional bike users than for e-bike users (35.0% vs 22.4%, p<0.001). In a multiple regression model, the odds of reaching the physical activity target were lower for e-biking than for conventional biking (OR=0.56; 95% CI 0.43 to 0.72) with age, sex, comorbidities and bike usage patterns as confounding factors. No significant differences were observed between bike groups for traffic accidents, yet when controlled for cycling time and frequency of cycling e-bikers had a higher risk of a traffic accident (OR=1.63; 95% CI 1.02 to 2.58). Conclusion: E-bikes are associated with a lower probability of reaching WHO targets for MVPA due to reduced duration and a reduced cardiovascular effort during riding. However, e-bikes might facilitate active transportation, particularly in older individuals or those with pre-existing conditions.